AHG v. Canada. (2018) - Unknown
Abstract : Human rights — Whether author's claims sufficiently substantiated — Whether author's claims incompatible ratione materiae with International Covenant on Civil and Political Rights, 1966 — Whether deportation in violation of obligations of State Party under Covenant — Right to life — Prohibition of torture and cruel, inhuman or degrading treatment — Right to liberty and security of person — Right to privacy and family — Whether State Party violating its obligations under Article 7 of Covenant — Effective remedy — Compensation International tribunals — Provisional measures of protection — Duty of compliance — United Nations Human Rights Committee — Indication of provisional measures — Compliance necessary as part of good faith participation in system of individual communications — United Nations Human Rights Committee